From inclusion to engagement: the psychological safety role in mediating inclusive leadership and diversity initiatives in the Indonesian workplace - Fahrizal, Indra; Budiono, Aris; Khalid, Jamaluddin; Santoso, Budi (Goodwood Publishing, 2025)
Purpose: This study explores how inclusive leadership and Diversity, Equity, and Inclusion (DEI) initiatives influence employee engagement and how psychological safety acts as a mediating factor. Methodology/approach: This study used quantitative research methodology. Data were analyzed using SmartPLS 4.0 from a sample of 151 participants who participated in this study between August and October 2024 from private, government, and service organizations in Indonesia. The questionnaire used Likert scales to collect quantitative data on the constructs of interest, including inclusive leadership, DEI initiatives, psychological safety, and work engagement Results/findings: The findings reveal that inclusive leadership and well-implemented DEI initiatives significantly enhance employee engagement, largely through the sense of psychological safety they foster. Employees who feel psychologically safe and confident in contributing ideas or expressing concerns without fear maintain higer levels of engagement in their work. Conclusions: The findings of this study provide actionable insights for practitioners and policymakers, suggesting that fostering psychological safety through inclusive leadership and DEI initiatives can be a strategic approach to improving employee engagement. Limitations: the study is limited by its reliance on self-reported data, a cross-sectional research design, and a focus on primarily service-related sectors in Indonesia, which restrict its generalizability. Future research should address these limitations by adopting longitudinal designs and exploring diverse industries and cultural settings to validate and extend these findings. Contribution: This study provides a substantial addition to the extant literature on leadership, diversity and inclusion (DEI), and psychological safety by highlighting the intricate interactions between these concepts and their influence on employee motivation and performance. Companies are encouraged to implement inclusive leadership practices and DEI programs to nurture an organizational culture where employees feel confident in expressing their authentic opinions without fear of negative consequences.